2022
DOI: 10.3389/fspor.2022.965195
|View full text |Cite
|
Sign up to set email alerts
|

A review of the essential visual skills required for soccer: Beyond 20–20 optometry

Abstract: In ball sports such as soccer, the visual system is critical in guiding a player's search for crucial information that underpins skillful behavior, which requires the incorporation of all of the relevant information in the environment in order to make successful decisions under pressure. However, vision in sport, and focusing on the specific visual skills required to be successful in a particular sport has largely been a practice ignored by experts and coaches as being an essential component of athletic perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…All visual skills discussed in this review are classified based on whether they meet the requirements of visual hardware or software skills. Visual hardware skills include [ 1 ] ( Table 1 ) visual acuity [ 13 - 16 ], depth perception [ 17 - 20 ], fusion flexibility [ 21 - 25 ], and contrast sensitivity [ 23 , 25 , 26 ]; visual software skills [ 1 ] ( Table 2 ) include eye tracking [ 27 - 31 ], hand-eye coordination [ 19 , 21 , 32 - 36 ], eye focusing [ 15 , 21 , 37 - 43 ], peripheral vision [ 17 , 19 , 34 , 44 - 47 ], speed and span of recognition [ 22 , 23 , 38 , 48 - 50 ], visual response time [ 24 , 25 , 51 - 53 ], and visual memory [ 24 , 50 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…All visual skills discussed in this review are classified based on whether they meet the requirements of visual hardware or software skills. Visual hardware skills include [ 1 ] ( Table 1 ) visual acuity [ 13 - 16 ], depth perception [ 17 - 20 ], fusion flexibility [ 21 - 25 ], and contrast sensitivity [ 23 , 25 , 26 ]; visual software skills [ 1 ] ( Table 2 ) include eye tracking [ 27 - 31 ], hand-eye coordination [ 19 , 21 , 32 - 36 ], eye focusing [ 15 , 21 , 37 - 43 ], peripheral vision [ 17 , 19 , 34 , 44 - 47 ], speed and span of recognition [ 22 , 23 , 38 , 48 - 50 ], visual response time [ 24 , 25 , 51 - 53 ], and visual memory [ 24 , 50 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that PA can modulate the excitability of the primary motor cortex, parietal cortex, and cerebellum influencing their related functions such as visuospatial and spatiotemporal skills as well as postural control [ 21 , [28] , [29] , [30] ]. In soccer, visual skills such as peripheral vision, depth perception, visual reaction time, and visual tracking of a moving object are of fundamental importance for players [ 13 , [15] , [16] , [17] , [18] ]. In fact, many research groups have demonstrated the influence of visual training on sport performance in soccer players [ 13 , [15] , [16] , [17] , [18] ].…”
Section: Discussionmentioning
confidence: 99%
“…In soccer, visual skills such as peripheral vision, depth perception, visual reaction time, and visual tracking of a moving object are of fundamental importance for players [ 13 , [15] , [16] , [17] , [18] ]. In fact, many research groups have demonstrated the influence of visual training on sport performance in soccer players [ 13 , [15] , [16] , [17] , [18] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to some recent studies by various authors ( Bauer et al, 2022 ; Kryeziu et al, 2023 ; Mohammadi-Nia et al, 2023 ; Osipov et al, 2023 ; Wu et al, 2023 ; Yuksel et al, 2020 ) that have examined different exercise programs in children and their different effects on PF, the importance of understanding these relationships in the context of child development is becoming increasingly clear. Speed is a central component of PF and refers to the ability to perform movements quickly and efficiently ( Barbieri et al, 2022 ; Fernandez-Fernandez et al, 2023 ; Jafar et al, 2023 ; Volk et al, 2023 ). Although it may appear to make a smaller contribution to health and long-term disease prevention, the importance of speed should not be underestimated, especially in the developmental phase of 8–to 9-year-olds ( Herszage et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%